การนำเหตุหลุดพ้นความรับผิดโดยเคร่งครัดของผู้ประกอบการยามาใช้ในกฎหมายไทย - ภัทราพรรณ เชื้อจินดา (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The Product Liability Act B.E. 2551 adopted the strict liability doctrine to hold entrepreneurs liable to the injured persons for damages caused by unsafe products to provide consumers a right to compensation without necessity to prove willfulness or negligence of the entrepreneurs. According to the study of this thesis, drugs and vaccines also fall within the definition of "Product" under this Act. Their characteristics, however, are different from the other categories of product because, firstly, drugs are one of the four requisites for livelihood. Secondly, drugs, due to their inherent dangers, cannot be made perfectly safe since dangers can be caused by various factors including, the drugs themselves, consumers, or even environmental factors. Pharmaceutical manufacturers, then, despite having used all available knowledge in the manufacturing of their products, could not remove all dangers arising from the use of drugs. Thirdly, the distribution of drugs contain a special method that is via the learnt intermediaries, medical professionals, who posses knowledge required to weigh the potential harms and benefits before prescribing any drug to a particular patient. Therefore, the Act’s strict liability doctrine may negatively affect Thai pharmaceutical industry in the future. Hence, the author would like to seek for an approach to modify the Act in order to make the liability of pharmaceutical manufacturers more appropriate and flexible for the specific nature of the pharmaceutical industry. The thesis will compare the enforcement approaches of the American, European Union and Japanese product liability laws but will mainly focus on the American approach due to its long history of development of the law. Furthermore, the thesis will concentrate on an appropriate compensation approach for the injured persons from drug side effects and adverse effects in Thailand.